2017
DOI: 10.2196/resprot.7151
|View full text |Cite
|
Sign up to set email alerts
|

Writing for Health: Rationale and Protocol for a Randomized Controlled Trial of Internet-Based Benefit-Finding Writing for Adults With Type 1 or Type 2 Diabetes

Abstract: BackgroundDiabetes mellitus is Australia’s fastest growing chronic disease, and has high comorbidity with depression. Both subthreshold depression and diabetes distress are common amongst people with type 1 or type 2 diabetes, and are associated with poorer diabetes self-care. A need exists for low-intensity self-help interventions for large numbers of people with diabetes and diabetes distress or subthreshold depression, as part of a stepped-care approach to meeting the psychological needs of people with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Two participants in the BFW group (8%) and two in the CW group (4%) were contacted by email following a high distress rating (≥5/6); all four participants reported that their distress was short-lived. Four participants in the BFW group (17%) and two in the CW group (4%) were contacted by telephone due to elevated scores on the PHQ-9 or GAD-7 at follow-up(s), in line with the study safety protocol [61]. One participant (in the BFW group) was referred to a mental health service after reporting a recurrence of previous depression at the 3-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two participants in the BFW group (8%) and two in the CW group (4%) were contacted by email following a high distress rating (≥5/6); all four participants reported that their distress was short-lived. Four participants in the BFW group (17%) and two in the CW group (4%) were contacted by telephone due to elevated scores on the PHQ-9 or GAD-7 at follow-up(s), in line with the study safety protocol [61]. One participant (in the BFW group) was referred to a mental health service after reporting a recurrence of previous depression at the 3-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The design consisted of a CONSORT-EHEALTH [60]–compliant, 2 (conditions) x 3 (time) RCT (Multimedia Appendix 1). The protocol for the trial has been published [61]. Participants were randomized to either internet-based BFW or internet-based CW (use-of-time writing).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies also make an important theoretical contribution to the literature on expressive writing theory. Previous positive writing instructions in literature on expressive writing have mainly focused on writing exclusively about positive experiences related to a distressing event (e.g., Crawford et al, 2017;Facchin et al 2014;Lichtenthal and Cruess, 2010;McCullough et al, 2006) or writing about a positive event (Baikie et al, 2012;Burton & King, 2004). However, according to research (Graci et al, 2018), a balance between the positive and the negative may be more essential.…”
Section: Discussionmentioning
confidence: 99%